Pontus and the Outside World : Studies in Black Sea History, Historiography, and Archaeology - Tuplin, Christopher, (Colloquia Pontica ;, 2004)
This volume presents ten papers on the Greek and non-Greek world of the Black Sea in the archaic, classical, Hellenistic and Roman periods. Five papers broach literary and historical topics. Four investigate material in Greek writers (Alcman, Aristeas of Proconnesus, Herodotus and Lucian) connected with Scythia and the North, while the fifth deals with the Bosporan Kingdom. Mediterranean Greek contact with, and reception of, the Pontic world play a significant role throughout. The other five papers concern pottery and metalwork (vessels and phalerae ) from Colchis, the North Black Sea and elsewhere. Some new material for the West is published (from Vani and Picvnari) but light is also cast on familiar objects (Sarmatian gold vessels) and iconography (Amazonomachies). Contact between the Aegean and Pontus is again a recurrent theme.